2007
DOI: 10.1093/rheumatology/kem319
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric lupus and reversible posterior leucoencephalopathy syndrome: a challenging clinical dilemma

Abstract: Reversible posterior leucoencephalopathy syndrome (RPLS) has been increasingly recognized and reported in the literature. While the condition has been well described in patients with acute hypertension, pre-eclampsia, eclampsia, post-transplantation and chemotherapy, RPLS has been increasingly identified in patients with autoimmune diseases such as systemic lupus erythematosus (SLE). Though experience in the diagnosis and management of RPLS in patients with SLE is likely accumulating, few have systematically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 53 publications
5
48
0
4
Order By: Relevance
“…Some authors suggest PRES is best considered a secondary complication of SLE or its treatment rather than SLE as a direct cause (4). Given the combined features of neurological symptoms and typical imaging findings in this entity, Mak et al proposed an algorithm for the diagnosis of this condition (5). In a review of 17 SLE cases with PRES, they concluded that urgent brain MRI and initiation of immediate treatment for PRES with very tight blood pressure control and antiepileptic medication are the mainstay of management.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest PRES is best considered a secondary complication of SLE or its treatment rather than SLE as a direct cause (4). Given the combined features of neurological symptoms and typical imaging findings in this entity, Mak et al proposed an algorithm for the diagnosis of this condition (5). In a review of 17 SLE cases with PRES, they concluded that urgent brain MRI and initiation of immediate treatment for PRES with very tight blood pressure control and antiepileptic medication are the mainstay of management.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 Un 20%-95% de pacientes con LES tienen manifestaciones neurológicas agrupadas bajo la denominación de lupus neuropsiquiátrico (LNPS) y pueden ser la forma de presentación del LES con escasos síntomas sistémicos. 6,15 Las manifestaciones clínicas son similares a la EPR y, por lo tanto, difíciles de diferenciar. Se recomienda el uso de la resonancia magnética para llegar a un diagnóstico de certeza y planear el tratamiento correspondiente.…”
Section: Discussionunclassified
“…Se recomienda el uso de la resonancia magnética para llegar a un diagnóstico de certeza y planear el tratamiento correspondiente. 1,15 Los diagnósticos diferenciales más importantes incluyen accidente cerebrovascular, trombosis de senos venosos y meningoencefalitis aséptica e infecciosa, 1 descartados en nuestra paciente sobre la base de la radiología y los análisis de laboratorio. Se desestimó tuberculosis cerebral por estos métodos diagnósticos y la evolución clínica.…”
Section: Discussionunclassified
“…It can occur as a result of conditions such as eclampsia, hypertensive encephalopathy, and intense immunosuppression [168]. Patients with SLE and systemic vasculitis s have been reported to present with PRES [169], and a distinction between 2 subtypes of PRES in SLE, inflammatory and hypertensive, has been proposed [170].…”
Section: Posterior Reversible Encephalopathy Syndromementioning
confidence: 99%
“…Often, escalation of immunosuppression can aggravate symptoms instead of resolving them [171]. However, in patients with SLE with high disease activity, a reduction of immunosuppression is usually not advocated, as the participation of inflammatory mechanisms is highly likely [168,172].…”
Section: Posterior Reversible Encephalopathy Syndromementioning
confidence: 99%